IMPLEMENTATION INQUIRY LEARNING MODEL TO IMPROVE SKILLS TRAINING PROCESS COST OF DISCUSSION ON SCIENCE IN MOTION STRAIGHT SMA NEGERI 1 NAMORAMBE - Suhaila Hasibuan; Purwanto Purwanto (Jurnal Pendidikan Fisika, 2018)
research aims knowing implementation Training Inquiry learning model to improve science process skills on the subject of the motion straight at SMA Negeri 1 Namorambe. This research was quasi experiment. The population empirically are all first semester students of class X SMA Negeri 1 Namorambe. Samples were taken using cluster random sampling technique, which is a class X MIA-2 as the experimental class learning model treated Inquiry Training, and Class X MIA-3 as a control group treated with conventional learning model with each class numbered 36 students. The research instrument is a test description as much as 9 question, and the activity of science process skills. Data were analyzed using normality test, homogeneity, and median equality test (test two parties and one party t-test) and test N-gain. The average value pretest experimental classes and control classes 30.50 and 30.05 respectively. The average value obtained postes both classes respectively 76.3 and 68.4. Both classes have a variation in normal distribution and homogeneous. Results observation science process skills activities experimental class students increased by an average of 5.5% every KPS. The test results test two parties obtained t = 0.233 and t table = 1.997 (t <t table), this suggests that the ability of the same early in the second grade. The test results of the t test obtained t = 4.593 and t table = 1.671 (t> t table), so there is a significant effect of the learning model Inquiry Training to improve science process skills on the subject of the motion straight at SMA Negeri 1 Namorambe.